Lesson study: Improving the quality of learning through on flipped classroom learning model - Sugiarni, Rani; Septian, Ari; Inayah, Sarah (UNIVERSITAS NEGERI MALANG, 2022)
This research purpose is to improve the quality of learning through the learning model of flipping the classroom on the subject of mathematics. This research is an export research by applying lesson study which consists of three intentions, namely planning , Do, and See. The subjects of this study were students of the Mathematics Education Study Program who took the Kapita Selekta Mathematics course. Research data collection instruments consisted of observation sheets, tests, and questionnaires. During the lecture process, observations were made of student activities both online and offline (face to face). To see the cognitive abilities given by test students and to see students' responses to the planning and implementation of a questionnaire The quality of learning is seen to increase from the online and offline activities of students and lecturer activities in class that encourage the activeness of the average value and classical absorption, which experiences improvement. Likewise, most of the students' responses were positive to the planning and implementation of learning taking place with the student learning model turned centered on class.